POWERSPRING SEBAGAI SOLUSI INOVATIF PEMBELAJARAN YANG ASYIK DAN MENYENANGKAN DI RUMAH SELAMA PANDEMI COVID-19 BAGI SISWA SD - nur hadi (Tunas Nusantara, 2020)
The formulation of the best practice problem is how the implementation of Powerspring learning can arouse the enthusiasm for learning at home during the COVID-19 pandemic and what are the results of the impact of changes in student behavior after learning using Powerspring. The purpose of writing is to determine the implementation of Powerspring learning can generate enthusiasm for learning and the results of the impact of changes in student behavior after learning using Powerspring. Powerspring application can stimulate students' enthusiasm for learning in elementary schools. There is a change in the behavior of students learning fun and enjoyable while studying at home. It is recommended to use the Powerspring application in home learning during the COVID-19 pandemic.Keywords: Powerspring, Innovative learning Solutions. fun and enjoyable